Strategies for the management of irrigation with saline water and nitrogen fertilization in millet crop - de Có , Erickson Gomes (2023)
It is believed that nitrogen fertilization will attenuate the salt stress on pearl millet plants. Thus, the objective was to evaluate the agronomic performance of the millet crop under different saline water irrigation strategies and nitrogen fertilization. The experimental design adopted was completely randomized (CRD), in a 4 x 2 factorial scheme, with 4 replicates, with the first factor being four irrigation strategies: S1 = low-salinity water (W1) = 0.3 dS m-1 throughout the cycle; S2 = saline water (W2) = 4.0 dS m-1 from 30 days after sowing - DAS; S3 = W2 from 45 DAS; and S4 = W2 from 65 DAS; and the second factor being two nitrogen doses (60 and 120 kg ha-1 of N). At the end of the experiment, the following variables were evaluated: photosynthesis, transpiration, stomatal conductance, instantaneous water use efficiency, internal CO2 concentration, leaf temperature, plant height, stem diameter, root length, panicle length, leaf dry mass, stem dry mass and root dry mass. Fertilization with 60 and 120 kg ha-1 promotes greater photosynthesis, transpiration, stomatal conductance and internal CO2 concentration in millet plants under the strategies S1, S2 and S3. The strategies S1 and S4 were more efficient to increase the efficient use of water and reduce leaf temperature.